SEMANTIC FEATURES OF SYNTACSIS CONSTRUCTIONS - Saparbaeva, N B; Anipina А К (Journal of Oriental Studies, 2016)
In recent years, China has been developing very rapidly, and every day increases the number of learners of the Chinese language. Chinese belongs to one of the oldest languages and is currently the language uses the ancient writing. Since the Chinese language is amorphous, its grammar is different from the grammars of other languages. The syntax of the Chinese language is enriched nominative construction. To be more precise, the main role is occupied structure, binding offer. In this paper a more detailed explanation of the semantic features of the syntax.